Government policy and private investment in Brazil (1955/82) - Ronci, Marcio Valerio (1987)
The question of the crowding-out of private investment by public expenditure, public investment in particular, in the Brazilian economy has been discussed more in ideological terrns than on empirical grounds. The present paper tries to avoid the limitation of previous studies by estlmatlng an equation for private investment whlch makes it possible to evaluate the effect of economic policies on prlvate investment. The private lnvestment equation was deduced modifylng the optimal flexible accelerator medel (OFAM) incorporating some channels through which public expendlture influences privateinvestment. The OFAM consists in adding adjustment costs to the neoclassical theory of investrnent. The investment fuction deduced is quite general and has the following explanatory variables: relative prices (user cost of capitaljimput prices ratios), real interest rates, real product, public expenditures and lagged private stock of capital. The model was estimated for private manufacturing industry data. The procedure adopted in estimating the model was to begin with a model as general as possible and apply restrictions to the model's parameters and test their statistical significance. A complete diagnostic testing was also made in order to test the stability of estirnated equations. This procedure avoids' the shortcomings of estimating a model with a apriori restrictions on its parameters, which may lead to model misspecification. The main findings of the present study were: the increase in public expenditure, at least in the long run, has in general a positive expectation effect on private investment greater than its crowding-out effect on priva te investment owing to the simultaneous rise in interst rates; a change in economlc policy, such as that one of Geisel administration, may have an important effect on private lnvestment; and reI ative prices are relevant in determining the leveI of desired stock of capital and private investrnent.